1989
DOI: 10.1002/mmnz.19890650111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Males on the Numerical Response of Diaeretiella rapae (M'Intosh) (Hym., Aphidiidae), a Parasitoid of Lipaphis erysimi Kalt. (Hem., Aphididae)

Abstract: The number of emerging offspring was affected by the density of the female parasitoid and the co‐presence of males along with the females. Parasitisation rates were evaluated in 5 × 1.7 cm petri dishes at parasitoid densities 1, 2, 4, and 8 females only and males mixed with same numbers of females. The mean number of parasitoid progeny with 1, 2, 4, and 8 female densities were 41.0, 48.6, 61.6, and 75.0 while with the introduction of equal number of males it decreased to 26.8, 37.0, 50.6, and 64.6, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 44 publications
4
10
0
1
Order By: Relevance
“…We observed that the offspring sex ratio in D. rapae decreased with age, and hence ovipositional activity, despite the continuous presence of males. This result supports the assertion that the sperm supply of females is not replenished, and is in accordance with the observations of other authors (King, 1987;Abidi et al, 1990). Other factors known to influence the offspring sex ratio in aphidiids (e.g., the number of previous matings by the male, beginning of oviposition [i.e.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We observed that the offspring sex ratio in D. rapae decreased with age, and hence ovipositional activity, despite the continuous presence of males. This result supports the assertion that the sperm supply of females is not replenished, and is in accordance with the observations of other authors (King, 1987;Abidi et al, 1990). Other factors known to influence the offspring sex ratio in aphidiids (e.g., the number of previous matings by the male, beginning of oviposition [i.e.…”
Section: Discussionsupporting
confidence: 92%
“…data) found that females of a D. rapae population from Iran, when offered honey and water in the absence of hosts, lived 23:8 0:8 and 6:0 0:4 days at 10.0 and 21.1 C, respectively; males lived 17:8 1:1and 4:9 0:5 days at the same temperatures, respectively. The mean longevity of D. rapae at the temperatures studied here are comparable in some cases, but not in others, to those previously reported by other authors (Hafez, 1961;Sedlag, 1964;Sethumadhavan & Dharmadhikari, 1969;Fukui & Takada, 1988;Abidi et al, 1990;Hayakawa et al, 1990;Reed et al, 1992) for different populations of this parasite under various sets of experimental conditions. The preoviposition period in female aphidiids is influenced by the prevailing environmental conditions, including temperature (Stáry, 1970).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This negative value shows an inverse relationship between parasitoid density and per capita searching efficiency. The negative relationship between per capita searching efficiency and parasitoid density was also documented in D. rapae on B. brassicae [29], and Lipaphis erysimi (Kaltenbach) [48,49]. This reaction refers to intraspecific competition in the parasitoids.…”
Section: Mutual Interferencementioning
confidence: 83%